A Partial Replacement of Fine Aggregate by Copper Slag In Concrete (International Journal of Engineering and Computer Science, 2018)
Many countries are witnessing a rapid growth in the construction industry which involves the use of natural resources for the development of the infrastructure. In order to reduce dependence on natural aggregates as the main source of aggregate in concrete, artificially manufactured aggregates and artificial aggregates generated from industrial wastes provide an alternative for the construction industry. In this study we are using copper slag as a partial replacement to fine aggregates in concrete, in which cubes were casted for various grades of concrete and for various proportions of sand replacement with copper slag ranging from 20% to 50%. Obtained results on different parameters like strength, workability and density were compared with those of control concrete made with ordinary Portland cement and sand.